Circulating β-d-Glucan as a Marker of Subclinical Coronary Plaque in Antiretroviral Therapy-Treated People With Human Immunodeficiency Virus. (7th March 2021) - Isnard, Stéphane; Fombuena, Brandon; Sadouni, Manel; Lin, John; Richard, Corentin; Routy, Bertrand; Ouyang, Jing; Ramendra, Rayoun; Peng, Xiaorong; Zhang, Yonglong; Finkelman, Malcolm; Tremblay-Sher, Daniel; et al.
Abstract: Background: Despite antiretroviral therapy (ART), people with human immunodeficiency virus (PWH) have increased risk of inflammatory comorbidities, including cardiovascular diseases. Gut epithelial damage, and translocation of bacterial lipopolysaccharide (LPS) or fungal β-d -glucan (BDG) drive inflammation in ART-treated PWH. In this study, we investigated whether markers of gut damage and microbial translocation were associated with cardiovascular risk in asymptomatic ART-treated PWH. Methods: We cross-sectionally analyzed plasma from 93 ART-treated PWH and 52 uninfected controls older than 40 years of age from the Canadian HIV and Aging Cohort. Participants were cardiovascular disease free and underwent a cardiac computed tomography (CT) to measure total coronary atherosclerotic plaque volume (TPV). Levels of bacterial LPS and gut damage markers REG3α and I-FABP were measured by enzyme-linked immunosorbent assay. Fungal BDG levels were analyzed using the Fungitell assay. Results: β-d -glucan levels but not LPS were significantly elevated in ART-treated PWH with coronary artery plaque ( P =  .0007). Moreover, BDG but not LPS levels correlated with TPV (r = 0.26, P =  .01). Intestinal fatty acid binding protein (I-FABP) but not REG3α levels correlated with TPV (r = 0.23, P  = .03). However, BDG and LPS levels were not elevated in uninfected controls with plaque. In multivariable models, elevated BDG levels were independently associated with the presence of coronary atherosclerosis in PWH but not in uninfected controls. Conclusions: Translocation of fungal BDG was associated with coronary atherosclerosis assessed by CT-scan imaging in ART-treated PWH, suggesting a human immunodeficiency virus-specific pathway leading to cardiovascular disease. Further investigation is needed to appraise causality of this association. Translocation of fungal products may represent a therapeutic target to prevent cardiovascular disease in ART-treated PWH. Plasma levels of the fungal product β-D-Glucan, but not the bacterial product lipopolysaccharide, are associated with the presence and the size of subclinical coronary atherosclerosis plaque in people living with HIV taking antiretroviral therapy, independently of classical cardiovascular risk factors.